PENGARUH GOOD CORPORATE GOVERNANCE, STRUKTUR KEPEMILIKAN, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN - Wandari, Rosita; Djazuli, Atim (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This research was conducted in light of Indonesia’s low score in good corporate governance application and cases of bad corporate governance in 2020. The unfavorable instances involved PT Jiwasraya and PT Asabri, insurance companies. This is ironic since financial industry is one of investor’s favorite sectors. The objective of this study is to assess and analyze the effect of good corporate governance, ownership structure, and firm age on the financial performance of financial-sector companies listed on the Indonesia Stock Exchange in the period of 2016-2020. Applying purposive sampling technique, 18 companies were selected as the sample. The data of this research was analyzed using multiple linear regression. This study finds that the size of board of commissioners, managerial ownership, and firm size positively and significantly influence financial performance, that institutional ownership negatively and significantly affects the performance, and that the proportion of board of commissioners, size of board of directors, and audit committee do not significantly influence it. In general, the dimensions of good corporate governance are not quite influential on financial performance, while ownership structure and firm size significantly affect the performance.